2019
DOI: 10.1108/pr-12-2018-0523
|View full text |Cite
|
Sign up to set email alerts
|

When investment in employee development promotes knowledge sharing behavior in an uncertain post-Soviet context

Abstract: Purpose The purpose of this paper is to explore the effect of perceived investment in employee development (PIED) on knowledge sharing (KS) behavior by examining the mediating role of psychological capital and moderating role of organizational identification. Design/methodology/approach Questionnaires were used to collect data from 340 employees from largest MNCs working in Kazakhstan. Findings The results show that psychological capital mediates the relationship between PIED and knowledge sharing behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Therefore, we reject Hypothesis 5 which proposes a direct relationship between OID and IWB and accept Hypothesis 6. We also found support for Hypothesis 7, since the direct effect of OID on IWB after introducing IM is not significant (Kozhakhmet et al, 2019). Moreover, the variance accounted for (VAF) index was calculated to be 0.478 [2] (Hadi et al, 2016), which indicated that 47.8 % of the total effect of OID is mediated by the indirect effect of IM.…”
Section: Structural Modelsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, we reject Hypothesis 5 which proposes a direct relationship between OID and IWB and accept Hypothesis 6. We also found support for Hypothesis 7, since the direct effect of OID on IWB after introducing IM is not significant (Kozhakhmet et al, 2019). Moreover, the variance accounted for (VAF) index was calculated to be 0.478 [2] (Hadi et al, 2016), which indicated that 47.8 % of the total effect of OID is mediated by the indirect effect of IM.…”
Section: Structural Modelsupporting
confidence: 61%
“…Moreover, the variance accounted for (VAF) index was calculated to be 0.478 [2] (Hadi et al , 2016), which indicated that 47.8 % of the total effect of OID is mediated by the indirect effect of IM. Therefore, we may conclude that our results indicate that IM partially mediates (VAF within 20 and 80 percent) the relationship between OID and IWB (Kozhakhmet et al , 2019), and H7 is partially supported.…”
Section: Discussionmentioning
confidence: 55%
“…Team EI mediates the relationship between leaders' emotional intelligence and team performance 3.2 Leader emotional intelligence, knowledge-sharing behavior and team performance Knowledge sharing is an important area of concern for interdisciplinary teams which is influenced by numerous leadership and team composition factors (Hu et al, 2018;Kim and Yun, 2015;Mesmer-Magnus and Dechurch, 2009;Seba et al, 2012;Yeow et al, 2019). A research study by Kozhakhmet et al (2019) inferred that organizational employees are not forced to adopt knowledge-sharing behavior rather it can be stimulated by creating such an environment. The role of the leader endeavors to describe how the exchange of information has an impact on knowledge sharing attitudes and behaviors for accomplishing team tasks.…”
Section: Leader Emotional Intelligence Team Emotional Intelligence An...mentioning
confidence: 99%
“…[2,3] By inducing interactions to gather and exchange knowledge, human capital contributes to the growth of innovation. [4,5] To use human resource management as a tool for performance management, it is important to know the basic principles that allow employees to be involved in these management processes. [6] The human capital costs can be considered as certain investments that are made by companies to improve human activity.…”
Section: The Essence Of Human Capitalmentioning
confidence: 99%